Cancer-related fatigue shows a stable association with diurnal cortisol dysregulation in breast cancer patients - Schmidt, Martina; Semik, Johanna; Habermann, Nina; Wiskemann, Joachim; Ulrich, Cornelia; Steindorf, Karen (Brain, behavior and immunity, 2016)
Fatigue is a major burden for breast cancer patients undergoing adjuvant therapy. Yet, its pathophysiology is still not well understood. Hypothesized mechanisms include dysregulations in the hypothalamic-pituitary-adrenal (HPA) axis, which may be reflected in alterations in the diurnal cortisol patterns. However, studies on the association between cortisol and fatigue during adjuvant cancer therapy are rare.
Available online 9 October 2015
Gesehen am 19.05.2020